PENERAPAN MODEL PENYELIDIKAN KELOMPOK DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Putri Gustia (ADISAM PUBLISHER, 2026)
This study aims to examine the implementation of the Group Investigation learning model in improving elementary school students’ critical thinking skills. The research employs a qualitative approach using library research by reviewing books, scientific journals, and previous studies relevant to the topic. Data were collected through reading, note-taking, and classifying relevant information, and then analyzed using content analysis techniques. The findings indicate that the Group Investigation model encourages students to actively seek information, engage in discussions, analyze problems, and draw logical conclusions. These processes contribute to developing critical thinking indicators such as identifying problems, evaluating information, providing logical arguments, and making rational decisions. Therefore, the Group Investigation model can serve as an effective alternative learning strategy to foster critical thinking skills at the elementary school level.